PENGKAYAAN MIKRONUTRIENT SILIKA DARI LIMBAH KACA PADA PUPUK ORGANIC CAIR DARI KULIT IKAN KAMBING-KAMBING (Albalistes stellaris) SERTA APLIKASINYA PADA TANAMAN KANGKUNG - Muhammad Kalil; Liya Handayani; Rulita Maulidya (Lembaga Riset dan Inovasi Kreyat Center, 2025)
Goatfish (Albalites stellaris) is one of the by-catch that is currently only consumed by filleting while the skin is simply thrown away. However, according to several studies, goatfish skin still has high protein and is used to make gelatin. The current shortage of POC circulating in the market has a silica deficiency so that plants do not have sufficient nutrients. This study aims to examine the silica contained in rice husk ash and how to apply POC with goatfish skin and added rice husk ash to kale plants. The research method used is the nonparametric Kruskal-Wallis Test with the SPPS application version 25, the implementation of the manufacture of POC from goatfish skin waste was analyzed by XRF tests, C (carbon), N (nitrogen), P (phosphorus), K (potassium) levels and application to plants. The results of the study showed that P2 had higher macro and micro nutrient content than P1, especially Potassium (K): 28.76% (P2) vs 14.02% (P1), Calcium (Ca): 31.50% (P2) vs 18.36% (P1), Phosphorus (P): 15.55% (P2) vs 11.93% (P1) Zinc (Zn): 0.65% (P2) vs 0.30% (P1). Although P1 is high in Silicon (40.35%), the main elements that support fast growth and green leaves in kale such as K, P, Fe, and Zn are higher in P2. POC from goat-goat fish skin waste without P2 rice husk ash is superior because the higher content of K, P, Ca, Zn, and Fe is very good for the vegetative growth of kale (fast-growing, wide, fresh green leaves) supports photosynthesis, stem strength, and plant resistance. Waste goat-goat fish skin (Albalistes stellaris) can be utilized as a liquid organic fertilizer using traditional fermentation. The addition of rice husk ash to the liquid organic fertilizer of goat-goat fish skin has an effect on growth. Application to kale plants with a comparison of silica and non-silica is known that the best growth of kale plants is on liquid organic fertilizer containing silica at a dose of 3 m1/L.